Characterisation of cell traction force in micropatterned tissues - Cheng, Yu Jun (Nanyang Technological University, 2022)
Tissue engineering is a field of medical science that researches for alternative methods to promote the regeneration of damaged cells and the creation of new tissues. As many medical treatments are performed in vivo, it is difficult to analyse the cellular activities occurring within the body. Therefore, in vitro model is introduced in tissue engineering to understand the behavioural change of a cell in an environment outside of the living organism. By analysing micropatterned tissue, the relationship between the shape pattern and the cell-to-cell interactions will be examined. Traction force microscopy (TFM) is a technique used in tissue engineering to calculate the traction force in cellular activities from the displacement of fluorescence beads. As cell-to-cell interactions require traction forces, performing TFM on micropatterned tissue would provide quantitative traction forces value for the interpretation of patterned cell behaviour. A circular pair pattern and an elongated shape pattern were designed in this experiment. After conducting TFM on the different pattern designs, it was revealed that the traction forces were exerted on the boundary of the furthest edge. From the trend of the traction force result, the phenomenon of cell dipole was introduced as a hypothesis for the cause of the trend. The circular pair pattern resulted in the formation of a cell bridge and was compared with the elongated pattern to understand how different designs affect the traction forces. Lastly, modifications and recommendations for this research are subsequently discussed.